2016
DOI: 10.1364/oe.24.025211
|View full text |Cite
|
Sign up to set email alerts
|

Distributed shape sensing using Brillouin scattering in multi-core fibers

Abstract: A theoretical and experimental study on the response of Brillouin scattering in multi-core optical fibers (MCF) under different curving conditions is presented. Results demonstrate that the Brillouin frequency shift of the off-center cores in MCF is highly bending-dependent, showing a linear dependence on the fiber curvature. This feature is here exploited to develop a new kind of distributed optical fiber sensor, which provides measurements of a distributed profile mapping the longitudinal fiber shape. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(74 citation statements)
references
References 17 publications
0
68
0
Order By: Relevance
“…They suggested that the change in coefficients largely can be attributed to practical differences in the core materials. Zhao et al [125,126] showed that the Brillouin scattering response of multi-core fibers is highly sensitive to bending, thus paving the way for three-dimensional shape sensors.…”
Section: Fiber Configurationsmentioning
confidence: 99%
“…They suggested that the change in coefficients largely can be attributed to practical differences in the core materials. Zhao et al [125,126] showed that the Brillouin scattering response of multi-core fibers is highly sensitive to bending, thus paving the way for three-dimensional shape sensors.…”
Section: Fiber Configurationsmentioning
confidence: 99%
“…µm In distributed measurements based on the Brillouin scattering effect, backcoupled light with shifted frequency is observed. This frequency shift, called Brillouin Frequency Shift (BFS), is a value which is constant in unchanged external conditions for a given fiber and is defined as 1,2 where is the effective refractive index, is the acoustic wave velocity and is the incident wavelength.…”
Section: Principlementioning
confidence: 99%
“…Hence, the BFS can be expressed using the mentioned relation for strain where is a variation of the BFS in the i-th core and is an initial BFS value in reference conditions (in the case of the MCF7 the BFS for central core can be used). Based on this relation and acquiring BFS measurements for at least 3 lateral cores, it is possible to determine the bend radius and orientation at each point along the fiber in the 3D space 1,17 .…”
Section: Principlementioning
confidence: 99%
See 2 more Smart Citations